Simultaneous Analysis of Hadith Quality About Salam Eliminating The Feeling of Oppression in The Book of Ḍaif Adab Al-Mufrad by Muhammad Nashiruddin Al-Albani - Indhra Musthofa; Mohammad Hakim (Al-Bukhari : Jurnal Ilmu Hadis, 2020)
The second source of Islamic values after Qur'an was hadith. Hadith was a credible source to explain the Qur'an which was still global. But in choosing a credible hadith to be used as a source of reference, must go through many stages, one of which is the quality of hadith. The quality of the hadith was a major consideration in an Islamic source. A hadith narrator named who in certain works has the quality of authentic traditions, but in other works he was judged to be ḍaīf by other scholars' hadiths. The article will discuss about the hadith about the greetings of al-Bukhārī in the book Adāb al-Mufrād which was judged to ḍaīf be by Naṣhīruddīn al-Albānī through criticizing his hadith in the Ḍaīf Adāb al-Mufrād book. This article tries to review the criticisms made by al-Albānī with the hadith research method simultaneously. Criticism of hadith that will be carried out has a specificity in assessing the quality of a hadith, because it was not only through criticism of matan and sanad, but also considers understanding in a hadith. So, this article will find the degree of a hadith which was discussed by considering the compatibility and meaning of a hadith.